Multi-omics analysis and single-cell sequencing revealed the lysosome associated molecular subtypes and prognostic model development of papillary thyroid carcinoma - Jianhua Zhang; Kai Yue; Yansheng Wu; Chao Jing; Xudong Wang (PLoS ONE, 2025)
Papillary thyroid carcinoma (PTC) is the most common endocrine carcinoma in recent years, necessitating more precise risk stratification to accurately identify low-risk patients. Although preliminary evidence exists, studies on lysosomes in PTC are limited. This study utilized multi-omics data from the TCGA database to comprehensively investigate the genomic and biological characteristics of lysosomes in PTC patients and identify lysosome-associated genes (LAGs) linked to PTC prognosis. We developed a LAG scoring system for risk stratification based on the expression levels of risk coefficients and independent prognostic LAG variables. Clinical value was assessed through immune infiltration analysis, pathological subgroup analysis, immunotherapy response, and drug sensitivity prediction. Single-cell sequencing from the GEO database was used to analyze PTC samples, and bioinformatics findings were validated using western blot, qRT-PCR, colony formation, and Transwell assays. A new LAG scoring system was developed based on five prognostic LAGs, with single-cell sequencing revealing their expression in different cell types. The role of one LAG, DNASE2B, in PTC cell cloning, proliferation, and invasion was further confirmed in vitro. This comprehensive study highlights the complex interactions between lysosomes and PTC biology, offering new insights into the role of lysosomes in PTC and identifying potential targets for intervention.